Modifying Food Texture for the Older Adult - Wendy J. Dahl (EDIS)
FSHN10-08, a 3-page illustrated fact sheet by Wendy J. Dahl, discusses information on altering food texture for older adults, and offers tips for enhancing puréed and ground foods. Includes references. Published by the UF Department of Food Science and Human Nutrition, July 2010.